B56-Associated Protein Phosphatase 2A Is Required For Survival and Protects from Apoptosis in Drosophila melanogaster - Li, Xinghai (American Society for Microbiology, 2002)
Protein phosphorylation and specific protein kinases can initiate signal transduction pathways leading to programmed cell death. The specific protein phosphatases regulating apoptosis have been more elusive. Using double-stranded RNA-mediated interference (RNAi), the role of protein phosphatase 2A (PP2A) in cellular signaling was investigated. Knockdown of A or C subunits individually or of combined B subunits led to concurrent loss of nontargeted PP2A subunits, suggesting that PP2A is an obligate heterotrimer in vivo. Global knockdown of PP2A activity or specific loss of redundant B56 regulatory subunits caused cell death with the morphological and biochemical changes characteristic of apoptosis in cultured S2 cells. B56:PP2A-regulated apoptosis required caspases and the upstream regulators dark, reaper, head involution defective, and dp53. In Drosophila embryos, knockdown of B56-regulated PP2A activity resulted in apoptosis and failure of gastrulation, an effect that was blocked by concurrent RNAi of the caspase Drice. B56-regulated PP2A activity appears to be required upstream of dp53 to maintain a critical proapoptotic substrate in a dephosphorylated, inactive state, thereby preventing apoptosis in Drosophila S2 cells.